Environmental tax reform in a federation with rent-induced migration - Jean-Denis Garon; Charles Séguin (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We study the welfare e↵ects of a revenue-neutral environmental tax reform in a federation. The reform consists of increasing a tax on a polluting input and reducing that on labor income. Households are fully mobile within the federation. Regions are unequally endowed with a nonrenewable natural resource. Resource rents are owned by regions and are redistributed to citizens on a residence basis, which generates a motive for inefficiently relocating to the resource-rich jurisdiction. Since the resource-poor region has a higher marginal product of labor than does the resource-rich region in equilibrium, the tax reform mitigates the scope of inefficient migration. This positive welfare e↵ect may significantly reduce fiscal costs of pollution pricing and calls for higher environmental tax, as compared with a model where migration is assumed away.
Keywords: 330